Protein and lysine requirements for maintenance and for tissue accretion in Atlantic salmon (Salmo salar) fry - Abboudi, Tarik; Mambrini, Muriel; Ooghe, Wilfried; Larondelle, Yvan; Rollin, Xavier (Aquaculture, 2006)
Available data on the quantitative requirement for lysine (Lys) in different salmonids show much variability. So far, there are very limited data on the maintenance requirements of indispensable (1) amino acids (AA) in fish. In the present study, we determined simultaneously the Lys requirements for maintenance and for protein accretion in Atlantic salmon fry by adapting a protocol established for the piglet. Groups of fish having an initial body weight of 1.5 g were fed for 28 days on isoenergetic diets with increasing nitrogen (N) content supplied by cod meal and a mixture of crystalline AAs (50% of total dietary N). Except the protein-free diet (PF; 0.2% dry matter (DM)), the N content of the other diets was either low (2.9% DM), medium (6.2% DM) or high (8.5% DM). Two types of diets with the same N content were formulated. The AA pattern of three control diets was based on the AA pattern of the cod meal protein. For the other three diets, Lys(.)HCl was totally omitted from the low-N diet (LPD), and 50% of Lys(.)HCl was removed from the medium- and high-N diets. After a 28-day feeding trial, carcass N and Lys gains were estimated. N and Lys requirements for maintenance and for growth were calculated regressing daily N or Lys gain against N or Lys intakes. The daily N requirement for growth above maintenance was 3.05 g per g protein gain and for maintenance it was 54 mg kg body weight(-0.75). From the regression between protein and Lys intake, we calculated that for the accretion of I g body protein, the dietary Lys requirement was 152 mg, and that the Lys maintenance requirement for zero N gain was 20 mg kg body weight(-0.75)/day. This last value is higher than the previous estimations obtained for rainbow trout and could be explained by the lower body weight or age of the fish used here. (c) 2006 Elsevier B.V. All rights reserved.